2018
DOI: 10.21608/edj.2018.77333
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Using Two Splinted Mini-Implants Versus Two Conventional Implants Retaining Mandibular Overdenture On Crestal Bone Loss

Abstract: Objective: was to compare the marginal bone loss around two splinted Mini-implants and two conventional implants retaining mandibular overdenture.Material and methods: Fourteen completely edentulous male patients were selected from those attended the out-patient clinic of Removable Prosthodontic Department, Faculty of Dentistry-Ain Shams University to participate in this study. Based on the cone beam computed tomographic (CBCT) assessment, the selected patients were divided into two equal groups: Group (I):Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…When the influence of implant diameter was considered, Mini implants produced the highest stresses and strains in both axial and off-axial loading when compared to conventional implants since the mini implants have a smaller surface area and volume, putting more stress per square millimetre against the bone than larger diameter implants [23] . However, the difference in the marginal bone loss was clinically insignificant [24] . A systematic review by Ma et al [25] showed that for early loaded implants, the average marginal bone loss was between 0 to 2 mm during the first year.…”
Section: Discussionmentioning
confidence: 93%
“…When the influence of implant diameter was considered, Mini implants produced the highest stresses and strains in both axial and off-axial loading when compared to conventional implants since the mini implants have a smaller surface area and volume, putting more stress per square millimetre against the bone than larger diameter implants [23] . However, the difference in the marginal bone loss was clinically insignificant [24] . A systematic review by Ma et al [25] showed that for early loaded implants, the average marginal bone loss was between 0 to 2 mm during the first year.…”
Section: Discussionmentioning
confidence: 93%